2014
DOI: 10.1182/blood-2013-10-528737
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inhibitor formation against FVIII in a murine model of hemophilia A by oral delivery of antigens bioencapsulated in plant cells

Abstract: • Factor VIII antigens can be expressed in chloroplasts and bioencapsulated in plant cells.• Oral delivery of plant cells expressing FVIII domains suppresses and reverses inhibitor formation in mice with hemophilia A by induction of CD4 1 regulatory T cells.Hemophilia A is the X-linked bleeding disorder caused by deficiency of coagulation factor VIII (FVIII). To address serious complications of inhibitory antibody formation in current replacement therapy, we created tobacco transplastomic lines expressing FVII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
130
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 48 publications
3
130
0
Order By: Relevance
“…Likewise, oral delivery of myelin basic protein reduced Ab plaques in advanced mouse and human Alzheimer's brains (Kohli et al, 2014). Delivery of coagulation factors to hemophilic mice induced oral tolerance and suppressed inhibitor formation and anaphylaxis Sherman et al, 2014;Wang et al, 2015a). The aforementioned examples illustrate the significance of this novel, cost-effective protein drug-delivery concept.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Likewise, oral delivery of myelin basic protein reduced Ab plaques in advanced mouse and human Alzheimer's brains (Kohli et al, 2014). Delivery of coagulation factors to hemophilic mice induced oral tolerance and suppressed inhibitor formation and anaphylaxis Sherman et al, 2014;Wang et al, 2015a). The aforementioned examples illustrate the significance of this novel, cost-effective protein drug-delivery concept.…”
mentioning
confidence: 97%
“…The native sequence of FVIII HC was amplified using the pAAV-TTR-hF8 mini plasmid (Sherman et al, 2014) as the PCR template. The codon-optimized HC sequence obtained using Codon Optimizer version 2.1 was synthesized by GenScript.…”
Section: Creation Of Transplastomic Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers behind the bio engineered lettuce have shown that inhibitor formation and severe allergic reactions can be prevented in mice by feeding the animals with a product based on these plants 1,2 . If the strategy also works in Anita and her kennel mates -and ultimately in humans -it could form the basis of the first product to protect against the immune responses associated with haemophilia treatment.…”
mentioning
confidence: 99%